2008
DOI: 10.1073/pnas.0712135105
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cells, lymphopenia, and IL-7 in a multistep pathway to autoimmunity

Abstract: There are many inhibitory mechanisms that function at the cellular and molecular levels to maintain tolerance. Despite this, self-reactive clones escape regulatory mechanisms and cause autoimmunity in certain circumstances. We hypothesized that the same mechanisms that permit T cells to expand during homeostatic proliferation may inadvertently promote autoimmunity under certain conditions. One major homeostatic cytokine is IL-7, and studies have linked it or its receptor to the development of multiple sclerosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 46 publications
4
104
1
Order By: Relevance
“…Increased serum IL-7 levels also were described in patients with different autoimmune diseases (15,16,36). Of interest, studies on rheumatoid arthritis and juvenile idiopathic arthritis indicated that augmented IL-7 counteracts the suppressive properties of CD4 + CD25 + CD127 low FOXP3 + regulatory T cells (Tregs) (37)(38)(39).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased serum IL-7 levels also were described in patients with different autoimmune diseases (15,16,36). Of interest, studies on rheumatoid arthritis and juvenile idiopathic arthritis indicated that augmented IL-7 counteracts the suppressive properties of CD4 + CD25 + CD127 low FOXP3 + regulatory T cells (Tregs) (37)(38)(39).…”
Section: Discussionmentioning
confidence: 98%
“…As a growth factor, IL-7 is involved in the maintenance of naive and memory CD4 + and CD8 + T cells (12)(13)(14). Of note, the level of circulating IL-7 is enhanced in response to lymphopenia in a variety of autoimmune disorders and as a result of chemotherapy and irradiation-based conditioning regimens prior to HSCT (15)(16)(17)(18). In the context of HSCT, the elevated IL-7 serum concentrations were associated with the occurrence and grade of acute GvHD (19)(20)(21).…”
Section: Ouble-negative (Dn) T Cells Are Defined By the Expressionmentioning
confidence: 99%
“…Moreover, mild lymphopenia and compensatory IL-21-dependent homoeostatic proliferation in nonobese diabetic mice that are prone to the development of autoimmunity have been reported to promote type 1 diabetes 44,45 . Similarly, deregulated regulatory T-cell expansion in lymphopenic nonobese diabetic hosts contributes to the development of type 1 diabetes 46 , whereas IL-7-mediated T-cell LIP in lupus or type 1 diabetes predisposed mice enhances their progression to disease 47,48 . In this study we have established for the first time the potential for excessive naive T-cell responses to peptide-MHC in the context of acute lymphopenia to alter the TCR repertoire and contribute to the development of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although this connection bears great therapeutic potential, it also carries undeniable risks. Just as IL-7 treatment for chronic viral infections bears the risk for developing autoimmune diseases by thwarting immune regulation (8)(9)(10), blockade of the IL-7R might increase the susceptibility for certain infections or even cancer in humans. Therefore, the degree to which IL-7Rα actually induces immunosuppression, if at all, needs to be carefully investigated in the future.…”
Section: Pd-1 Pathway Largely Abrogates the Protective Effect Of Ilmentioning
confidence: 99%
“…In both cases, therapeutic administration of recombinant IL-7 enhanced the antigen-specific T-cell responses by amplifying survival and effector mechanisms and counteracting several inhibitory pathways, such as PD-1 (7,8). However, IL-7 has the unfortunate ability to promote the emergence of autoreactive T cells, and thus can be associated with the development of autoimmune diseases (9,10). The importance of IL-7 in the development of autoimmune disorders is further underlined by observations from genome-wide association studies that identified genetic variations of the IL-7Rα chain as risk factors for the development of T1D and multiple sclerosis (11,12).…”
mentioning
confidence: 99%